RECOGNITION AND LAUDATION FOR FACE SAVING ACT IN HARRY POTTER: THE HALF-BLOOD PRINCE - Veronika Listi Ferdini Damopolii (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The research analyzes recognation and laudation for Face Saving Act suggested by Leech (1993) dan Yule (1996). The goal of the of the analysis is to give a description of the intention of the speaker or speaker meaning when giving recognation and laudation all at once. This study analyzes whether the laud is used to avoid threats to one's self-image or vice versa. The research uses a qualitative descriptive method. The data analyzed by using pragmatic approach. The speakers, Professor Slughorn, Mrs. Weasley, and Ron Weasley used utterances catrgorized as Recognation and Laudation for Face Saving Act to reveal that recognation and laudation can be used to avoid possible threats to one's self-image. Those utterances of Recognation and Laudation for Face Saving Acti spoken by Professor Slughorn, Mrs. Weasley, Ron Weasley and Harry Potter are used to change the positive self-image from the perceived negative self-image thought by the hearer in this conversation.